Finding longitude: The Investigator expedition, 1801–1803. (November 2017) - Morgan, Kenneth
This article analyses the methods deployed for finding longitude on the Investigator 's expedition to circumnavigate Australia, made under the command of Matthew Flinders in the period 1801–1803. Timekeeping and astronomy were complementary methods for ascertaining longitude; they were carried out using chronometers and by taking lunar observations. The article explains who was responsible for handling the astronomical readings on the expedition; the performance of the chronometers used; Flinders's comparisons of the longitudinal readings with the work of previous navigators; and the reasons why dissemination of the longitudes taken during the voyage was delayed. The article shows how the combined use of chronometers and lunar observations helped Flinders to achieve scientific accuracy in his charting of coastal Australia in the atlas to his major work entitled A Voyage to Terra Australis .